Local Government Financial Performance Analysis Using Economic, Efficiensy and Effectiveness Ratio and it’s Affect Development of Jambi City - Friyani, Rita; Nurhayani, Nurhayani; Rosmeli, Rosmeli (Indonesian Journal of Business Analytics, 2023)
This research examines to assesses the financial performance of the Jambi City Government by using the calculation method of Economic Ratios, Efficiency Ratios and Effectiveness Ratios and to see the effect of this financial performance on development in Jambi City. The analytical method in this research uses descriptive analysis and Correlation Test. The data used in this study are Regional Expenditures, Personnel Expenditures, Capital Expenditures, Regional Revenues and Local Own Revenue for the City of Jambi for the last 4 years, namely 2018, 2019, 2020, and 2021. The three ratios from the value for money method are then linked with the Capital Expenditure growth ratio.